2020
DOI: 10.2147/ott.s250655
|View full text |Cite
|
Sign up to set email alerts
|

<p>Histamine H3 Receptor Promotes Cell Survival via Regulating PKA/CREB/CDKN1A Signal Pathway in Hepatocellular Carcinoma</p>

Abstract: Background: The histamine H3 receptor (HRH3) is mainly expressed in areas of the brain involved in the regulation of the release of various neurotransmitters. Recent studies have shown that HRH3 expression is increased in several types of carcinomas. However, the functional roles and underlying molecular mechanism by which HRH3 regulates cell survival in hepatocellular carcinoma (HCC) remain unknown. Methods: The mRNA and protein expression level of target genes were evaluated by qRT-PCR, Western blot and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…At the same time, inhibition of HRH3 inhibited the metastasis of HCC cells, further supporting the functional role of HRH3 in promoting the metastasis of malignant tumors, which indicates that increased HRH3 levels can be a potential prognostic marker for HCC patients ( Yu et al, 2019 ). Besides, HRH3 in HCC inactivates the cAMP/PKA/CREB pathway by down-regulating the expression of cyclin-dependent kinase inhibitor P21 (CDKN1A), promoting the G1-S phase transition, and ultimately promotes the malignant growth of HCC ( Zhang et al, 2020 ).…”
Section: The Role Of Mast Cells In Liver Cancermentioning
confidence: 99%
“…At the same time, inhibition of HRH3 inhibited the metastasis of HCC cells, further supporting the functional role of HRH3 in promoting the metastasis of malignant tumors, which indicates that increased HRH3 levels can be a potential prognostic marker for HCC patients ( Yu et al, 2019 ). Besides, HRH3 in HCC inactivates the cAMP/PKA/CREB pathway by down-regulating the expression of cyclin-dependent kinase inhibitor P21 (CDKN1A), promoting the G1-S phase transition, and ultimately promotes the malignant growth of HCC ( Zhang et al, 2020 ).…”
Section: The Role Of Mast Cells In Liver Cancermentioning
confidence: 99%
“…H3HR expression is elevated in HCC, promoting cell growth and survival through protein kinase/cyclic adenosine monophosphate responsive element-binding/cyclindependent kinase inhibitor p21 signaling. [16] The increase of tryptase-positive and chymase-positive MCs in human HCC [17] and the decrease in tryptase serum level in patients with HCC after hepatic transarterial chemoembolization [18] suggest a role for these as biomarkers. The majority of MCs in HCC are inactive, and resting MC density is elevated in 305 HCC livers using tryptase immunohistochemistry.…”
Section: Mcs and Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Several cell cyclerelated genes are regulated by p-CREB and p-AKT. [19][20][21][22] Knockdown of CREB induces cell cycle arrest and significantly reduces tumor cell proliferation. [23][24][25] Our research found that cyclin-dependent kinase inhibitors p21 and p27 were reduced in CSRP2 knockdown cells.…”
Section: Dovepressmentioning
confidence: 99%